Behavior Motives and Legal Study of Commercial Sex Workers Around Pemalang District Terminal Area - Gunawan, Riyan; Mahendra, Mirza Haris; Zakaria, Hilmi Rizki; Qoyum, Muhammad (Law Research Review Quarterly, 2020)
Prostitution comes from the word prostitutio which means things to place, confront, offer. There are also other articles selling, peddling, but generally interpreted as surrender to many people by getting a reward for fulfilling that section of the person. Prostitution or prostitution is a serious problem and needs improvements that need to improve society, this disease develops very rapidly in the community. In addition to the social forms of social norms, prostitution is also a form of immorality in any religion that is not permitted and rejected. Although prostitution is issued in religion or law, many of these prostitution practices occur in Indonesia. Prostitution is a lucrative and promising business place for so many people to believe in their pride. It is necessary to establish a new criminal law legislation to provide legal attention to the imposition of sanctions aimed at commercial sex workers and users of services. Because the criminal law currently in force in Indonesia is considered not in accordance with the current state of Indonesia.